2001
DOI: 10.1088/0957-0233/12/7/308
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of temperature and strain sensitivities of a two-mode Bragg grating imprinted in a bow-tie fibre

Abstract: A method for measuring the sensitivity of Bragg gratings to external parameters for different spatial and polarization modes is presented together with the results of measurements of sensitivity to temperature and elongation for LPx01, LPy01, LPx11 and LPy11 modes. The difference in response according to the type of mode shows the possibility of performing simultaneous temperature and elongation measurements using two-mode Bragg gratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…To overcome this difficulty we used a specially developed measurement system shown in Fig. 3a, which was earlier used for characterizing a two-mode Bragg grating imprinted in bow-tie fiber [12]. Transmision spectra of the inv€tigated grating obtained with a standard spectrum analyzer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this difficulty we used a specially developed measurement system shown in Fig. 3a, which was earlier used for characterizing a two-mode Bragg grating imprinted in bow-tie fiber [12]. Transmision spectra of the inv€tigated grating obtained with a standard spectrum analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…By measuring the location of the center of diffracted peak (for every polarization mode) versus the value of applied parameter, we could determine the grating sensitivity to temperature and pressure for both polarization modes. The numerical method of finding the location of the center of diffracted mode and the calibration procedure of diffracted spectrum were described in our earlier paper [12]. The wavelength resolution obtained in described experiment was equal to 15 pm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of multiparameter sensing with FBG written in Hi-bi fiber has been addressed by several researchers. For example Urbanczyk et al [4] demonstrated a sensor to simultaneously determine temperature and strain sensitivities using a two-mode Bragg grating imprinted in a bow-tie fiber. Guanghui Chen et al [5] described a sensor to simultaneously measure strain and temperature using FBG written in novel Hi-bi optical fiber.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid the multifiber solution to multiparameter sensing problems, a variety of other alternatives have been used. Techniques to discriminate sensing parameters include double superposed grating structures with different [1], FBGs in fiber with dissimilar diameters [2], utilization of the second-order diffraction from a saturated first-order 1550 nm grating [3], FBGs in birefringent fibers [4], etc. These techniques were developed mainly for the particular case of strain and temperature discrimination.…”
Section: Introductionmentioning
confidence: 99%